Sustainable Tourism and Development Communication of Bandung Barat Local Government - Limilia, Putri; Bona Pratamawaty, Benazir; Prihandini, Puji; Robert Rondonuwu, Roy (International Journal of Psychosocial Rehabilitation, 2020)
The importance of sustainable tourism development based is highly recommended in developing tourism destinations to ensure its sustainability in the future, including Bandung Barat tourism destinations. The significance of sustainable tourism approach in developing tourism destination needs to be supported by wellestablished development communication in order to involve all of the stakeholders, that is policy maker (local government), policy implementer (Office of Tourism and Culture), local people around the tourism destination area, and tourism agents. This study aims to investigate and analyse the development communication of Bandung Barat local government in developing tourism destination with sustainable tourism based. Methods used was qualitative with case study approach. Data collection incorporates observation of and interview with Bandung Barat Office of Tourism and Culture. Results indicate that Bandung Barat local government already have definitive understanding regards sustainable tourism. Moreover, they have applied the concept into policies of tourism development. Bandung Barat local government employs monolog development communication in developing sustainable tourism. This model emphasizes to increase the targeted societies’ knowledge and behavioural change without actively involved in the process. In addition, finding shows that in regards of development, Bandung Barat local government employs participation paradigm which is able to generate the society’s sense of belonging towards the programs running.